2016
DOI: 10.1155/2016/7895615
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Critical Slip Surface of Three-Dimensional Soil Slopes from the Stress Fields Solved Using the Finite Element Method

Abstract: The slope stability problem is an important issue for the safety of human beings and structures. The stability analysis of the three-dimensional (3D) slope is essential to prevent landslides, but the most important and difficult problem is how to determine the 3D critical slip surface with the minimum factor of safety in earth slopes. Basing on the slope stress field with the finite element method, a stability analysis method is proposed to determine the critical slip surface and the corresponding safety facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Cheng and Lau [11] adopted the simplified Bishop method and simplified Janbu method to study the influence of slope curvature on spherical damage of concave and convex slopes, and they concluded that compared with straight slope, the factor of safety (FS) of concave slopes and convex slopes are larger and smaller, respectively. Although these works predicted accurate enough FSs of concave and convex slopes, curved surfaces are necessary to be assumed for slip surfaces, such as cylindrical [12], spherical [13], and ellipsoidal [14]. More importantly, these postulated slip surfaces may not satisfy the flow law, thus predicting unrealistic FSs.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng and Lau [11] adopted the simplified Bishop method and simplified Janbu method to study the influence of slope curvature on spherical damage of concave and convex slopes, and they concluded that compared with straight slope, the factor of safety (FS) of concave slopes and convex slopes are larger and smaller, respectively. Although these works predicted accurate enough FSs of concave and convex slopes, curved surfaces are necessary to be assumed for slip surfaces, such as cylindrical [12], spherical [13], and ellipsoidal [14]. More importantly, these postulated slip surfaces may not satisfy the flow law, thus predicting unrealistic FSs.…”
Section: Introductionmentioning
confidence: 99%